Treatment in the absence of disease reclassification among men on active surveillance for prostate cancer. Issue 2 (13th September 2021) - Kirk, Peter S.; Zhu, Kehao; Zheng, Yingye; Newcomb, Lisa F.; Schenk, Jeannette M.; Brooks, James D.; Carroll, Peter R.; Dash, Atreya; Ellis, William J.; Filson, Christopher P.; Gleave, Martin E.; Liss, Michael; et al.
Abstract : Background: Maintaining men on active surveillance for prostate cancer can be challenging. Although most men who eventually undergo treatment have experienced clinical progression, a smaller subset elects treatment in the absence of disease reclassification. This study sought to understand factors associated with treatment in a large, contemporary, prospective cohort. Methods: This study identified 1789 men in the Canary Prostate Cancer Active Surveillance Study cohort enrolled as of 2020 with a median follow‐up of 5.6 years. Clinical and demographic data as well as information on patient‐reported quality of life and urinary symptoms were used in multivariable Cox proportional hazards regression models to identify factors associated with the time to treatment Results: Within 4 years of their diagnosis, 33% of men (95% confidence interval [CI], 30%‐35%) underwent treatment, and 10% (95% CI, 9%‐12%) were treated in the absence of reclassification. The most significant factor associated with any treatment was an increasing Gleason grade group (adjusted hazard ratio [aHR], 14.5; 95% CI, 11.7‐17.9). Urinary quality‐of‐life scores were associated with treatment without reclassification (aHR comparing "mostly dissatisfied/terrible" with "pleased/mixed, " 2.65; 95% CI, 1.54‐4.59). In a subset analysis (n = 692), married men, compared with single men, were more likely to undergo treatment in the absence of reclassification (aHR, 2.63; 95% CI, 1.04‐6.66). Conclusions: A substantial number of men with prostate cancer undergo treatment in the absence of clinical changes in their cancers, and quality‐of‐life changes and marital status may be important factors in these decisions. Lay Summary: This analysis of men on active surveillance for prostate cancer shows that approximately 1 in 10 men will decide to be treated within 4 years of their diagnosis even if their cancer is stable. These choices may be related in part to quality‐or‐life or spousal concerns. Abstract : Some men on active surveillance for prostate cancer will eventually choose to be treated even in the absence of clinical progression of their disease. These decisions may be driven in part by quality‐of‐life concerns or the involvement of spouses.